2018
DOI: 10.18632/oncotarget.24821
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-induced alterations in endometrial proteins crucial in recurrent miscarriages

Abstract: High androgen level impairs endometrial receptivity in women experiences the recurrent miscarriage. The mechanism of androgen actions on endometrium is still uncertain. We hypothesized that androgen has a direct effect on the endometrium in women with recurrent miscarriage. In the present study, we assess the impact of androgen (A2) at high concentration (10–7 M) on Ishikawa cells compared with the physiological concentration of androgen (10–9 M). To go into deeper analysis, we use global stable isotopes label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The proteins of the upstream regulators also play key roles in RM. Furthermore, p38 MAPK gene delays the implantation process by blocking these specific genes [19]. In the present study, proteomics analysis also showed that the p53 gene pathway was activated by increasing levels of A2, thereby downregulating NUCKS1.…”
Section: Discussionsupporting
confidence: 62%
“…The proteins of the upstream regulators also play key roles in RM. Furthermore, p38 MAPK gene delays the implantation process by blocking these specific genes [19]. In the present study, proteomics analysis also showed that the p53 gene pathway was activated by increasing levels of A2, thereby downregulating NUCKS1.…”
Section: Discussionsupporting
confidence: 62%
“…In 1988, Sagle et al [ 92 ] reported a high prevalence of PCOM in women who had recurrent miscarriages, which was later confirmed by other authors [ 93 ]. Additionally, available data emphasize the impact of HA on miscarriages [ 94 , 95 , 96 , 97 ], but the role of adrenal androgens has not been studied widely [ 98 , 99 , 100 ]. Moreover, reports concerning the predictive value of LH on miscarriage are distinct [ 93 , 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective nature of our study could be a limitation. Besides, the previous studies showed that excess androgen could also cause adverse effects on the reproductive outcome of IVF‐ET 23,24 . These paradoxical phenomena reveal that endometrial development and embryonic implantation of patients with severe endometriosis may require appropriate basal serum androgen concentration which needs further investigation.…”
Section: Discussionmentioning
confidence: 98%